Delayed Diagnosis of Perrault Syndrome: A Rare Genetic Disorder - Mirgul Bayanova; Aigerim Abilova; Alisa Nauryzbayeva; Zhibek Turarbekova (Case Reports in Medicine)
Perrault syndrome (PRLTS) is a rare autosomal recessive disorder which is associated with pathogenic variants in HSD17B4, HARS2, CLPP, LARS2, GGPS1, RMND1, TWNK, ERAL1, and PRORP genes. The disease is characterized by sensorineural hearing loss, sometimes with neurological signs, including progressive sensory and motor peripheral neuropathy, cerebellar ataxia, mild mental retardation, and ovarian dysgenesis in females. In this article, we report a case of a child diagnosed with spastic diplegic cerebral palsy. Determination of the segregation status of the parents of a proband with a rare compound heterozygote in the gene HSD17B4 will help the genetic counselling for the prognosis of Perrault syndrome in the family.